A higher aspect ratio enhanced bioaccumulation and altered immune responses due to intravenously-injected aluminum oxide nanoparticles. (3rd July 2016) - Park, Eun-Jung; Kim, Soo Nam; Kang, Min-Sung; Lee, Byoung-Seok; Yoon, Cheolho; Jeong, Uiseok; Kim, Younghun; Lee, Gwang-Hee; Kim, Dong-Wan; Kim, Jong Sung
Abstract: Aluminum oxide nanoparticles (AlO NP) have been widely utilized in a variety of areas, including in the optical, biomedical and electronic fields and in the overall development of nanotechnologies. However, their toxicological profiles are still not fully developed. This study compared the distribution and immunotoxicity of two rod-types of AlO NP. As reported previously, the two types of AlO NP had different aspect ratios (long-type: 6.2 ± 0.6, short-type: 2.1 ± 0.4), but the size and surface charge were very similar. On Day 14 after a single intravenous (IV) injection (1.25 or 5 mg/kg), both AlO NP accumulated primarily in the liver and spleen and altered the levels of redox response-related elements. The accumulated level was higher in mice exposed to the long-type AlO NP compared to the short-type. Additionally, it was noted that the levels of IL-1 β, IL-8 and MCP-1 were enhanced in the blood of mice exposed to both types of AlO NP and the percentages of neutrophils and monocytes among all white blood cells were increased only in mice injected with the long-type AlO NP (5 mg/kg). In addition, as compared to the control, co-expression of CD80 and CD86 (necessary for antigen presentation) on splenocytes together with a decreased expression of chemotaxis-related marker (CD195) was attenuated by exposure to the AlO NP, especially the long-type. Taken together, the data suggest that accumulation following a single IV injection with rod-types of AlO NP is strengthened by a high aspect ratio and, subsequently, this accumulation has the potential to influence immune functions in an exposed host.